Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Moderasi Pada Indeks Sri Kehati BEI - Aris Sunandes (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2020)
The purpose of this study was to examine: the effect of corporate social responsibility on firm value, the effect of capital structure on firm value and to know the ability of capital structure to moderate corporate social responsibility on firm value in companies listed on the Sri-Kehati Index. The research method uses the Moderated Regression Analysis model, purposive sampling with 25 companies two years of observation 2017-2018. The results of this study are the capital structure does not affect the value of the company, corporate social responsibility does not affect the value of the company, the potential capital structure in moderating the relationship of corporate social responsibility to the value of the company in companies listed on the Sri-Kehati Index.